Neuroendocrine differentiation in gastric adenocarcinomas; Correlation with tumor stage and expression of VEGF and p53 - (:unkn) unknown (SPRINGER, 2004)
Studies on neuroendocrine differentiation (NED) in conventional gastric adenocarcinomas and its significance on tumor behavior are limited. Our aim was to search for the expression of neuroendocrine differentiation in conventional gastric adenocarcinomas and correlate it with tumor type, stage and expression of VEGF and p53. Forty-two gastrectomy specimens with gastric adenocarcinoma were stained with chromogranin A to detect neuroendocrine differentiation and 45% of the cases were found to be NED (+). No significant correlation was found between NED and tumor type. However, NED was more frequent in advanced stage cases independently of tumor type. VEGF expression was also considerably more frequent in NED (+) tumors compared to NED (-) ones 84% vs. 56%). Moreover, we found a significant correlation between NED and the presence of lymph node metastases. P53 expression in NED (+) tumors was 68%. There was no significant correlation between VEGF and p53 in NED (+) cases. In conclusion, neuroendocrine differentiation is a frequent finding in conventional gastric adenocarcinomas, and although it does not seem to play a specific role in tumor progression, it seems that neuroendocrine cells are one of the factors contributing to angiogenesis by expressing VEGF, especially in advanced stage cases, affecting the incidence of lymph node metastases. Further studies with larger series should be performed to confirm this observation.
Keywords: gastric adenocarcinoma; neuroendocrine; p53; VEGF; CHROMOGRANIN-A EXPRESSION; PROGNOSTIC-SIGNIFICANCE; CELLS; ANGIOGENESIS; CANCER